In suspectis finibus: bolesti suviška legitimiteta - Ivić, Nenad (Array, 1998)
This paper examines the case of usurpation of Silvanus in the middle of the fourth century in Gaul as presented by the eye-witness historian Ammianus Marcellinus. It offers a thourough analysis of all extant contemporary sources and modern research replacing this relatively unimportant event in the complex web of relations between a center (the reigning legitimate emperor Constantius II) an the perifery (the military commanders in frontier-zones who acted as his deputies).